2010
DOI: 10.1259/dmfr/52763613
|View full text |Cite
|
Sign up to set email alerts
|

Flemish general dental practitioners' knowledge of dental radiology

Abstract: The aim of this study was to assess general dental practitioners' knowledge of dental radiography and radiation protection in order to alert the Belgian authorities and dental professional societies. Prior to attending a postgraduate course on intraoral radiology, general dental practitioners in Flanders, Belgium, were asked to fill in a questionnaire regarding the radiological equipment and the techniques they used for intraoral radiography. The availability and type of dental panoramic equipment were also as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
(20 reference statements)
4
31
0
4
Order By: Relevance
“…Various researchers5,9,11-13,18-20,22-25 have reported similar findings. Low scores in the practice domain of the present study may be attributed to the respondents' lack of knowledge of radiation hazards and protection measures.…”
Section: Discussionsupporting
confidence: 56%
“…Various researchers5,9,11-13,18-20,22-25 have reported similar findings. Low scores in the practice domain of the present study may be attributed to the respondents' lack of knowledge of radiation hazards and protection measures.…”
Section: Discussionsupporting
confidence: 56%
“…These are summarized in Table 1. 53 questionnaire studies were identified in the dental literature that concerned dental radiography and included a report of response rate. 1,2, These were all published between 1983 and 2010. In total, 87 articles are referred to in this review, including the 53 dental radiology studies.…”
Section: Resultsmentioning
confidence: 99%
“…They can provide important, cost-effective information on dentists' knowledge, attitudes and practices. [1][2][3] There have been several reviews or commentaries on the design of such studies. Nevertheless, the focus of these articles is overwhelmingly on the quantity of response, in other words non-response error.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] While the literature does include one study that evaluates the effectiveness of web-based instruction in the interpretation of anatomy using CBCT images, 12 no information appears in the literature regarding students' knowledge and attitudes about CBCT.…”
Section: Discussionmentioning
confidence: 99%